PCL–PEG graft copolymers with tunable amphiphilicity as efficient drug delivery systems. Issue 37 (8th September 2016) - Al Samad, A.; Bethry, A.; Koziolová, E.; Netopilík, M.; Etrych, T.; Bakkour, Y.; Coudane, J.; El Omar, F.; Nottelet, B.
Abstract : Efficient drug delivery systems are prepared, thanks to the fine-tuning of the amphiphilicity and architecture of PCL–PEG graft copolymers via a simple photochemical approach. Abstract : The development of flexible drug delivery systems that can be tuned as a function of the drug to be delivered and of the target disease is crucial in modern medicine. For this aim, novel amphiphilic poly(ε-caprolactone)- g -poly(ethylene glycol) (PCL- g -PEG) copolymers with well-controlled design were synthesized by thiol–yne photochemistry. The grafting density and the copolymer amphiphilicity were easily controlled via the reaction parameters: concentration, reaction time, PEG length and the molar ratio between PCL and PEG or the photoinitiator in the reaction mixture. The self-assembling behavior of the copolymers was studied and a correlation between the composition of PCL- g -PEG and the nanoaggregate diameter sizes (28 to 73 nm) and critical aggregation concentrations (1.1 to 4.3 mg L −1 ) was found. The influence of copolymer amphiphilicity on the drug loading was evaluated with various drugs including anticancer drugs (paclitaxel, ABT-199), drugs to overcome multidrug resistance in cancer cells (curcumin, elacridar), an anti-inflammatory drug (dexamethasone) and an antibacterial drug (clofazimine). Finally, the influence of amphiphilicity on curcumin release and toxicity towards MCF-7 cancer cell lines was studied. The impact of the grafting density, PEG length and the overall EG/CL ratio is discussed in detail. Curcumin loaded PCL- g -PEG with lower EG/CL ratios and shorter PEG chains showed higher toxicity compared to their more hydrophilic counterparts.